Peran Guru dan Orang Tua Terhadap Pembelajaran Pendidikan Agama Islam Melalui Blanded Learning - Ainul Khuriyah; Muhaiminah Darajat (Moderasi : Journal of Islamic Studies, 2021)
Blended learning is a combination of several aspects such as face-to-face with online learning, so this learning requires the role of a teacher and parents so that learning can be achieved effectively and efficiently. This study focuses on the role of teachers and parents in achieving Islamic religious education learning through blended learning. The method used in this study is a qualitative method with a descriptive approach. The data collected in the form of documents and words from interviews. Data collection techniques using observation, in-depth interviews and documentation through data analysis using the techniques proposed by Miles and Huberman (data reduction, data display and conclusion drawing/verification). From the results of the study, it can be concluded that the role of educators and parents in achieving the effectiveness of learning Islamic religious education through blended learning at MTs Nurul Masyithoh Lumajang is quite good. It also reflects that the role of teachers and parents in achieving the effectiveness of Islamic religious education learning through blended learning is quite good with the help of teachers and parents being mentors, facilitators and motivators.